Emerging imaging techniques for atherosclerosis in systemic immune-mediated inflammatory conditions - Markousis-Mavrogenis, George; Habib, Muzzamal; Huck, Daniel M.; André, Florian; Steen, Henning; Mukherjee, Monica; Mavrogeni, Sophie I.; Weber, Brittany (Arteriosclerosis, thrombosis, and vascular biology, 2025)
Atherosclerosis affects patients with systemic immune-mediated inflammatory diseases at an increased rate compared with the general population. In recent years, our understanding of the pathophysiology of atherosclerosis has advanced considerably. Nevertheless, cardiovascular imaging modalities that can adequately assess the biological background of atherosclerosis have not reached widespread clinical adoption. Novel developments in cardiac imaging have the potential to enhance the diagnostic yield of these modalities further while providing essential insights into the anatomy, composition, and biology of atherosclerotic lesions. In this review, we highlight some of the latest developments in the field for the evaluation of atherosclerosis using advances in echocardiography, computed tomography, positron emission tomography, and cardiovascular magnetic resonance. Additionally, we discuss evidence specifically in patients with immune-mediated inflammatory diseases and outline unmet research needs for future development.